2009
DOI: 10.2527/jas.2008-1036
|View full text |Cite
|
Sign up to set email alerts
|

Performance and digestibility characteristics of finishing diets containing distillers grains, composites of corn processing coproducts, or supplemental corn oil1

Abstract: ABSTRACT:Three experiments evaluated the lipids in distillers grains plus solubles compared with corn or other sources of lipid in finishing diets. Experiment 1 utilized 60 individually fed yearling heifers (349 ± 34 kg) fed treatments consisting of 0, 20, or 40% (DM basis) wet distillers grains plus solubles (WDGS), or 0, 2.5, or 5.0% (DM basis) corn oil in a finishing diet based on high-moisture corn (HMC) and dry-rolled corn (DRC). Cattle fed 20 and 40% WDGS had greater (P < 0.10) G:F than cattle fed 0% WDG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
4
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 34 publications
8
85
4
6
Order By: Relevance
“…The fat sources used, CSB and SOB at 3 and 5% of EE in the diet, did not affect (P ≥ 0.05) the carcass traits of the animals (Table 4), which is in agreement with Zinn (1989a), Felton andKerley (2004b), Cranston et al (2006), Larraín, Schaefer, Arp, Claus, and Reed (2009),Vander Pol et al (2009, who also found no changes in carcass traits using different fat sources in diets for feedlot cattle.…”
Section: Carcass Evaluationsupporting
confidence: 86%
See 1 more Smart Citation
“…The fat sources used, CSB and SOB at 3 and 5% of EE in the diet, did not affect (P ≥ 0.05) the carcass traits of the animals (Table 4), which is in agreement with Zinn (1989a), Felton andKerley (2004b), Cranston et al (2006), Larraín, Schaefer, Arp, Claus, and Reed (2009),Vander Pol et al (2009, who also found no changes in carcass traits using different fat sources in diets for feedlot cattle.…”
Section: Carcass Evaluationsupporting
confidence: 86%
“…Nevertheless, the same authors, in a second 72-day experiment, found no effect of increasing the EE content in diets on DM intake of animals. Vander Pol et al (2009) in two reported experiments with diets ranging from 3.5 to 8.8%EE also found no effect on DM intake of animals.…”
Section: Performancementioning
confidence: 91%
“…In the current experiment, the majority of the increase in CP in the DDGS diet was as a result of RUP and RUP was 67% of the CP in the DDGS diet and only 29% of the CP in the CON diet. Also, fat concentrations were elevated in the DDGS diets in the present experiment and a greater percentage of UFAs in DDGS have been reported to bypass ruminal biohydrogenation compared with control diets (Vander Pol et al, 2009). It has been proposed that fat supplementation, specifically PUFAs (Mattos et al, 2000), or a combination of both fat and CP (Engel et al, 2008;Gunn et al, 2014) improve reproductive performance.…”
Section: Shee Lemenager and Schoonmakermentioning
confidence: 45%
“…SCFA and MCFAs are mainly derived from de novo synthesis in the mammary gland, whereas LCFA are derived from the diet (Bauman and Griinari, 2003). DDGS contain elevated PUFA and LCFA, which are partially protected from ruminal biohydrogenation (Vander Pol et al, 2009). Additionally, PUFA can hinder de novo synthesis of SCFA and MCFA, resulting in an increased proportion of dietary LCFA in the milk (Bauman and Griinari, 2003).…”
Section: Milkmentioning
confidence: 99%
“…They are characterised by a high nutritive value for ruminants, owing to a high content of protein, a high contribution of dietary fi bre being well digestible by the ruminants, and -in the case of DDGS from maize -also by a considerable fat content. Thanks to those properties, the DDGSs may replace concentrates in feed rations for ruminants, and with appropriately balanced structural fi bre -they may also in part substitute for feed roughages [Cyriac et al, 2005;Vander Pol et al, 2009;Martin et al, 2007;Schingoethe, 2006]. In turn, due to a high content of protein, the DDGS may be applied in fatteners feeding as a substitute for high-protein feeds, e.g.…”
Section: Introductionmentioning
confidence: 99%